Use of indicators of oxidative stress and HSP 70 protein as markers in the diagnostics of dental diseases - Pavlov, S. V.; Samoilenko, A. V.; Vozna, I. V.; Павлов, Сергій Васильович; Возна, Ірина Володимирівна (publishing center of the ESCBM, The Czech Republic, 2018)
The most important triggering factor in the initiation of the pathological process is the formation of the dental plaque as a multilayered microbial biofilm with parodontopathogenic microorganisms. They include the causative agents of the chronic inflammatory process in the periodontal disease, such as Tanerella forsythensis, Porphyromonas gingivalis, Treponema denticola, and the inducer of acute aggressive inflammation of Actinobacillus actinomycetemcomitans.
Keywords: тези доповідей; parodontitis; nitrotyrosine; heat shock protein